Business Model Canvas dan Analisis SWOT untuk Meningkatkan Strategi Pemasaran Rumah Batik Anto Djamil - Rahmawati, Yulia Dwi; Setiawan, Ito (JUSIFO : Jurnal Sistem Informasi, 2022)
Rumah Batik Anto Djamil is a traditional batik shop in Banyumas, located in the Purwokerto area. Currently, the business conducts marketing through both physical stores and digital media. However, there are challenges in the form of increasing numbers of new competitors emerging. These competitors sell similar products with nearly identical marketing strategies. An initial blueprint was drawn up according to the business model currently employed by Rumah Batik Anto Djamil. This study aims to analyze and develop the business model of Rumah Batik Anto Djamil in order to compete in similar fields of business. Data was collected through interviews and observation. Then, the Business Model Canvas was designed to facilitate the analysis of new marketing strategies. SWOT analysis was chosen to identify strengths, weaknesses, opportunities, and future threats that may occur. This analysis considers both internal and external strategic factors. The results of the study include the current BMC blueprint, SWOT analysis, and recommended BMC blueprint for developing the business unit in the future. The conclusion of this study is that the recommendations given must continue to consider quality and service to customers and potential customers. This study has limitations, particularly when government regulations change and new digital business patterns using more popular platforms emerge.